Gender-Based Violence: A Crucial Challenge for Public Health - Sanjel, S (Kathmandu University Medical Journal, 2015)
This article attempts to summarize the situations of gender-based violence, a major public health issue. Due to the unequal power relations between men and women, women are violated either in family, in the community or in the State. Gender-based violence takes different forms like physical, sexual or psychological/ emotional violence. The causes of gender-based violence are multidimensional including social, economic, cultural, political and religious. The literatures written in relation to the gender-based violence are accessed using electronic databases as PubMed, Medline and Google scholar, Google and other Internet Websites between 1994 and first quarter of 2013. The keywords such as gender-based violence, women violence, domestic violence, wife abuse, violence during pregnancy, women sexual abuse, political gender based violence, cultural gender-based violence, economical gender-based violence, child sexual abuse and special forms of gender-based violence in Nepal were used for internet search. As GBVs remain one of the most rigorous challenges of women’s health and well-being, it is one of the indispensable issues of equity and social justice. To create a gender-based violence free environment, a lot works has to be done. Hence, it is suggested to provide assistance to the victims of violence developing the mechanism to support them. DOI: http://dx.doi.org/10.3126/kumj.v11i2.12499 Kathmandu University Medical Journal Vol.11(2) 2013: 179-184